Importancia de la educación física en la prevención de la obesidad infantil en los estudiantes del sexto grado de la Unidad Educativa Guillermo Baquerizo Jimenez - Martinez Torrez, Edison Alexander (2023)
Physical education plays a crucial role in the prevention of childhood obesity among sixth grade students at the Guillermo Baquerizo Jiménez Educational Unit and in all children in general. Physical education encourages students' active participation in sports and recreational activities, which helps increase their level of physical activity. This is essential to burn calories and maintain a healthy weight. Through physical education, students learn about the health benefits of exercise, such as preventing obesity, strengthening muscles and bones, and improving cardiovascular health. This helps them understand why it is vital to stay active. Participating in physical activities and sports in the physical education environment can increase students' self-esteem and confidence. This can help prevent childhood obesity, as children who feel secure are more likely to take care of themselves and their health. Childhood obesity can lead to a number of health problems. Physical education helps prevent excessive weight gain and therefore reduces the risk of these diseases. Physical education plays a critical role in preventing childhood obesity by encouraging physical activity, teaching essential skills, promoting awareness of the importance of exercise, and establishing healthy habits from an early age.